ANALISIS PENGARUH PRICE TO BOOK VALUE, INDEKS HARGA SAHAM GABUNGAN (IHSG) TERHADAP RETURN HARGA SAHAM SEBELUM DAN PADA SAAT PANDEMI PADA PERUSAHAAN TELEKOMUNIKASI - Ikrom, Ikrom; Suliswanto, Muhammad Sri Wahyudi; Fuddin, Muhammad Khoirul (Journal of Financial Economics & Investment, 2022)
The purpose of this study is to determine and analyze the effect of price to book value, the composite stock price index, and the covid-19 dummy on the stock price of the telecommunications sector per quarter in 2019-2020. This study uses panel data and hypothesis testing. The results of this study indicate that price to book value, the composite stock price index, and the covid-19 dummy have a positive and significant effect on stock prices in the telecommunications sector. This proves that if the stock price increases by 1%, the price to book value, the joint stock price index, and the dummy will also increase.